Efl Students’ Motivation on The Using of Code Mixing in The Classroom Interaction - Adisaturrahimi, Andi; Mustaqimah, Mustaqimah; Reskyani, Reskyani; Mohd Tahir, Asman Bin (Universitas Nahdlatul Ulama Blitar, 2024)
In bilingual communities, code mixing serves as a useful communication strategy between students and teachers. It is also an interesting topic to research when considering language as a medium for interaction and communication. In this study, the researcher focused on finding out whether the use of code mixing can enhance EFL students’ motivation in the classroom interaction or not. A descriptive qualitative method used for conducting this study. The researcher conducted this study at Institut Agama Islam Negeri (IAIN Bone). The participants were ten sixth semester of EFL students. The researcher used interview as the research instrument. The result showed that the use of code mixing can enhance students motivation. The positive impacts of using the code mixing were the material can easily be understood and the students’ vocabularies can increase by the time. The negative impact was it will make the students difficult to speak English fully.